KONSEP DISTRIBUSI KEKAYAAN PERSPEKTIF EKONOMI SYARIAH DALAM UPAYA PEMERATAAN KESEJAHTERAAN - Ningsih, Dian Wirna; Azzaki, Muhammad Adnan (An Nuqud Journal of Islamic Economics, 2025)
Wealth distribution inequality is a major challenge in modern economies, leading to growing social disparity and injustice. This article explores the concept of wealth distribution from the perspective of Islamic economics as a solution to achieving equitable welfare. Using a literature review approach, it examines the fundamental principles of wealth distribution in Islam, such as justice (`adl), balance (tawazun), and public interest (maslahah). It also discusses the role of Islamic instruments like zakat, infak, sadaqah, and waqf in the process of wealth redistribution. The study finds that Islamic economics offers a wealth distribution system that is not only economically fair but also rooted in spiritual and social values. The importance of synergy between society, zakat institutions, and the government is emphasized in creating a just and sustainable distribution system